(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
Alien species represent an important part of the crustaceans of Syrian fowl, which are about 128 species. The total number of migratory species in Syrian waters recorded in this work make up only 27 species. This number represents 21.5% of all marine Decapoda known in Syria and 38.8% of introduced species in the Mediterranean. Decapoda species introduced into Syria belong to 10 different families and are spread over 22 genera. The family Penaeidae and the family Portunidae are the most represented in introduced species with 7 for each. The Leucosiidae family ranks second by the number of species with 4 lessepsian and then the Pasiphaeidae and Alpheidae families represented by two species. Only one introduced species has been reported for the following families: Palinuridae, Majidae, Matutidae, Xantidae and Pilumnidae. Of the 27 species decapod found in Syria, 5 have been reported for the first time in the marine waters of this country during the last decade and two among this, registered in 2017 for the first time. These species are Melicertus hathor, Alpheus audouini, Arcania elongata, Matuta victor and Gonioinfradens paucidentatus. It is accepted that alien species may have ecological, economic or health related influences, especially after they succeed in establishing dense population, or presenting invasive characters. The invasion of exotic species on the Syrian coast by the Suez Canal plays also a big role in modifying the original specific composition of Syrian waters. تشكل الأنواع الغريبة جزءا هاما من فاونا القشريات عشاريات الأرجل في سورية و التي تعد حوالي 128 نوعا. إن إجمالي عدد الأنواع المهاجرة إلى المياه السورية و المسجلة في هذا العمل هو 27 نوعا فقط. يشكل هذا العدد حوالي 21.5 % من القشريات عشاريات الأرجل المعروفة في سورية و حوالي 38.8 % من الأنواع المهاجرة المعروفة في البحر الأبيض المتوسط. تتوزع هذه الأنواع على عشرة فصائل مختلفة و 22 جنساً و تعتبر فصيلة Portunidae و فصيلة Penaeidaeمن أكثر الفصائل تنوعا و ممثلة ب 7 أنواع لكل منها. تأتي بعدها فصيلة Leucosiidae ممثلة ب 4 أنواع مهاجرة في حين تم تسجيل نوعين مهاجرين لكل من فصيلة Pasiphaeidae وفصيلة Alpheidae , أما بقية الفصائل و عددها خمسة فقد تم تسجيل وجود نوع واحد لكل منها. بعض هذه الأنواع تم تسجيلة في المياه البحرية السورية خلال السنوات الأخيرة و هي النوع Melicertus hathor و النوع Alpheus audouini و النوع Arcania elongata و النوع Matuta victor و النوع Gonioinfradens paucidentatus. من المقبول أن الأنواع الغريبة لها تأثيرات مختلفة، خاصة بعد أن نجح بعضها في إنشاء مجتمعات كبيرة في الوسط الجديد. إن غزو الأنواع الغريبة للشاطئ السوري عن طريق قناة السويس لعب و ما زال يلعب دورا كبيرا في تعديل التركيبة الأصلية لفاونا القشريات عشاريات الأرجل في المياه السورية كما أن له نتائج اقتصادية وبيئية هامة.